Marx @ 2000 - NA, NA. author. aut Link
XIV, 164 p.
Keywords: Marx is out of fashion in intellectual circles on the whole but he is increasingly seen as an astute and relevant guide to the spread of a new raw capitalism world wide. This book is a timely and lively reappraisal of Marx and the socialist experience in the light of subsequent political and intellectual developments.